Penggunaan Hak Atas Tanah Lahan Gambut Yang Bersertifikat Hak Milik Sebagai Jaminan Kredit - Puspasari, Fitri; Lestari, Rika; Hasanah, Ulfia (State of Islamic Institute Langsa, 2023)
Property rights are hereditary, strongest and fullest rights that a person or legal entity can have over land keeping in mind social functions. Based on Article 20 of the UUPA it is stated that the distinguishing properties of property rights and other rights. Article 25 of the UUPA explains that property rights can be used as debt security by being burdened with dependent rights. In Law Number 4 of 1996 concerning Dependent Rights on land and objects related to land, it is stipulated that land rights can also be burdened with dependent rights when used as collateral to obtain credit at a bank. However, people in East Strait Village, Meranti Islands Regency cannot make property rights certificates as credit collateral. This article is classified as literature research with a qualitative approach. The methodology used is the study of normative law. The results of the study found that land owned by the community could not be charged with Right of Dependent. The Certificate of Dependent Rights cannot be issued because the land in the area is designated as included in the peat area or the PIPPIB map as stipulated in Presidential Instruction Number 5 of 2019 concerning the Termination of Granting New Permits and Improving the Management of Primary Natural Forests and Peatlands. The issuance of this Presidential Instruction is considered not in accordance with the authority of the holder of the title certificate as stipulated in the UUPA.